Pola asuh orang tua dari remaja dengan perilaku agresif di Desa Geger, Kabupaten Madiun - Lailatul Restu Suprihatin; Mayrina Eka Prasetyo Budi (ROSYADA: Islamic Guidance and Counseling, 2021)
Parenting is an important factor in shaping children’s behavior. Good parenting will make children behave well and vice versa. The phenomenon of adolescent aggressive behavior is often encountered in everyday life. The author is interested in conducting research related to teenage parenting and aggressive behavior. This research was conducted in Geger Village, Madiun district where there is a negative issue of adolescent behavior.This study aims to reveal the aggressive behavior of adolescents and various kinds of parenting styles in Geger Village . This research is qualitative with descriptive qualitative approach. The data collection technique was done by observing, interviewing and documenting. The data analysis technique is done by processing data, presenting data, and drawing conclusions. The validity or validity of the data is tested by triangulation techniques, including using the triangulation technique of data sources, methods, and theories.The results showed that from five subjects obtained several types of aggressive behavior. These types of aggressive behavior include direct-active-verbal, direct-active-non-verbal, direct-passive-non-verbal aggressive behavior. There were also aggressive behaviors that differed from different parenting styles. Keywords: Parenting patterns, Adolescent,  Aggressive behavior